2011
DOI: 10.1111/j.1463-1318.2011.02727.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of incidental colorectal tumours with 18F-labelled 2-fluoro-2-deoxyglucose positron emission tomography/computed tomography scans: results of a prospective study

Abstract: Our study proves the necessity of colonoscopy when incidental FDG uptake is found on PET/CT imaging. The false-positive FDG uptake is more commonly observed in the right colon. Although the SUVmax value is higher in cancer patients, a high SUVmax value does not necessarily result in malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
37
3
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 16 publications
10
37
3
10
Order By: Relevance
“…Peng et al prospectively looked at nearly 11,000 PET/CT scans, and found focal uptake in 148. Histological results were obtained for 136 of these patients: 23.5% had colorectal tumours and 20.5% polyps [15]. …”
Section: Discussionmentioning
confidence: 99%
“…Peng et al prospectively looked at nearly 11,000 PET/CT scans, and found focal uptake in 148. Histological results were obtained for 136 of these patients: 23.5% had colorectal tumours and 20.5% polyps [15]. …”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, advanced histology is not Table 3 Measures unequivocally more metabolically active 21 or detectable. 9 Peng et al 23 found among 23 patients with adenomatous polyps that the mean SUVmax was similar between those with and without advanced histology (p ¼ 0.119). Despite the prospective nature of that study, only 23 polyps were reported; whereas Gollub et al 9 showed that even polyps 10 mm with a villous component could be missed at optimized PET/CT colonoscopy.…”
Section: Discussionmentioning
confidence: 90%
“…An increasing number of patients undergo PET/CT as part of their oncological care, some having never been screened for colorectal cancer. Although incidental colonic uptake at PET/CT should be pursued, as per prior guidelines, 23 the lack of focal colonic uptake does not exclude the presence of important precursor lesions in the colon and unscreened patients aged 50 years without a family history will still need an approved screening examination. Although it could be interesting to pursue similar studies with other isotope tracers, the underlying low resolution of PET/CT, its slow imaging time, and thus, poor temporal resolution, high cost, and the myriad of artefacts that can interfere with detecting smaller lesions would argue against pursuing further investigation in this area.…”
Section: Discussionmentioning
confidence: 98%
“…PET can characterize benign or malign character of tumor correctly and diagnose metastases early (Kumar et al 2003). 18 F-FDG can be used in the diagnosis and evaluation of outcome prediction and disease extension in several tumors such as small cell lung cancer (Arslan et al 2011), head and neck canncers (Kondo et al 2011), extranodal lymphoma (Ilica et al 2011), cervical carcinoma (Cetina et al 2011), colorectal tumors (Peng et al 2011) and so on. Therefore, depening on its sensitivity the physician can decide therapy plan such as applying chemotherapy or surgery.…”
Section: Oncologymentioning
confidence: 99%